The mediating role of financial management behavior in the relationship between financial literacy and business performance - Dwijayanty, Rima; Buchory, Herry Achmad; Nuryaman, Nuryaman; Kusumah, Wedi Rusmawan (Edelweiss Applied Science and Technology, 2025)
This study investigates the mediating role of financial management behavior in the relationship between financial literacy and the business performance of Micro, Small, and Medium Enterprises (MSMEs) in West Java, Indonesia. Using a quantitative approach with SEM-AMOS and a purposive sample of 359 digital MSMEs, the research reveals that financial literacy has both a direct and indirect impact on business performance. However, over 80% of this effect is mediated by financial management behavior. These findings support behavioral finance theory and emphasize the importance of translating financial knowledge into actionable practices. The study contributes theoretically by validating the mediating mechanism in digital MSMEs and offers practical insights for policy development and MSME training programs.